Computers and information processing QuickBASIC edition - Fuller, Floyd (Boyd & Fraser Pub. Co., 1994)
Examines various aspects of computers and data processing, including the components and functions of computer hardware, the applications of software, information processing systems, and the legal and social issues involved.